History on the Screen: From Fact to Fiction. Ways of Presenting the Past and Constructing Characters in Polish Feature Films on Modern History after the Year 2010 - Urbańska, Magdalena (Media - Culture - Social Communication, 2019)
The article reviews Polish cinematographic works of fiction about the most recent history created since 2010. Since the early 2000s, Polish cinema has introduced a new narrative of the national identity by analyzing its past. Since 2010 historical cinema has presented an increasing number of fictional characters and has depicted history in very diverse manners. The following article is comprised of three sections, each of them elaborating on a particular model of historical representation: factographical realism, fictional characters in factographical movies and historical works of fiction. Each type’s distinctive functions and characteristics are analyzed, while taking into consideration the embedment of characters in historical realities and focusing on the most important motives, which are shown in particular film examples. The author’s main motivation is to discuss the development in contemporary Polish cinema and recent changes in historical movies by tracing its recurring themes, such as national mythology and remembrance.